Enhancing Strategies for Improving Safety Risk Management in Fabricated Residential Construction: A Neutrosophic Approach to Minimize Hazards and Ensure Efficiency - Lijie Yang (Neutrosophic Sets and Systems)
Safety risk management in fabricated residential construction persists as an important yet challenging task because of the inherent uncertainties, ambiguities, and complexities associated with construction projects. Traditional risk management approaches often struggle to adequately capture these uncertainties, leading to suboptimal decision-making. In response to this gap, this paper proposes a novel Interval-Valued Fermatean Neutrosophic Set (IVFNS)-based ELECTRE II method for improving safety risk management. The proposed method integrates the strengths of IVFNS, which effectively models uncertainty, indeterminacy, and inconsistency, with the ELECTRE II outranking approach, which provides a structured framework for ranking alternatives based on pairwise comparisons. A public case study from a real construction company is introduced, involving five fabricated residential construction projects, to demonstrate and analyze the applicability of different safety techniques under different choice factors. The quantitative and qualitative analysis demonstrate that our methodology can offer a new solution to advance risk management in fabricated residential construction.